2019
DOI: 10.3390/cancers11121958
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Molecules as Prognostic Biomarkers for Acute Myeloid Leukemia

Abstract: The role of Notch signaling in acute myeloid leukemia (AML) is still under investigation. We have previously shown that high levels of Notch receptors and ligands could interfere with drug response. In this study, the protein expression of 79 AML blast samples collected from newly diagnosed patients was examined through flow cytometry. Gamma-secretase inhibitors were used in AML mouse xenograft models to evaluate the contribution of Notch pharmacological inhibition to mouse survival. We used univariate analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Notably, in a recent study we found that less mature AML subtypes (M0-M1) expressed high levels of all the four receptors (Notch1–4) and some ligands (Jagged2, DLL-3), whereas adverse cytogenetic risk groups overexpressed Notch3, Notch4, and Jagged2 as compared to good cytogenetic risk patients. Accordingly, univariate and multivariate analysis confirmed a longer overall survival for patients presenting low expression of Notch4, Jagged2, and DLL3 on leukemia cells at diagnosis ( Takam Kamga et al, 2019a ).…”
Section: Msc-derived Notch and Wnt Signaling In Leukemiamentioning
confidence: 81%
See 3 more Smart Citations
“…Notably, in a recent study we found that less mature AML subtypes (M0-M1) expressed high levels of all the four receptors (Notch1–4) and some ligands (Jagged2, DLL-3), whereas adverse cytogenetic risk groups overexpressed Notch3, Notch4, and Jagged2 as compared to good cytogenetic risk patients. Accordingly, univariate and multivariate analysis confirmed a longer overall survival for patients presenting low expression of Notch4, Jagged2, and DLL3 on leukemia cells at diagnosis ( Takam Kamga et al, 2019a ).…”
Section: Msc-derived Notch and Wnt Signaling In Leukemiamentioning
confidence: 81%
“…Putting in the context of anti-leukemic treatment, epigenetic analysis of blast cells collected from B-ALL patients along the course of the disease revealed that the methylation pattern of Notch receptors’ genes changes according to the disease step. It was observed that Notch genes receptors are highly methylated at diagnosis, less methylated upon drug treatment and became hypermethylated in relapsed patients ( Takam Kamga et al, 2019a ). These observations suggested that the methylation status of Notch genes might be relevant for drug response.…”
Section: Msc-derived Notch and Wnt Signaling In Leukemiamentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike T-ALL, activating NOTCH1 mutations in AML are rarely found; however, overexpression of Notch 1 and its ligands have been shown to be independent prognostic markers of overall patient survival [ 56 , 57 , 58 , 59 ]. In a recent AML study, Notch 3, 4 and Jagged-1 were associated with an adverse cytogeneic risk, Notch 2 and 3 expression were associated with increased relapse following induction therapy, Notch 4 and Jagged-2 were associated with increased relapse following allogeneic stem cell transplantation, while Notch 4, Jagged-2 and DLL-3 expression were associated with a poor OS in AML patients, further supporting the biomarker and therapeutic potential of Notch in this cancer [ 60 ].…”
Section: Notch In Cancer: An Overviewmentioning
confidence: 89%